2022
DOI: 10.3390/ijerph19063326
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vibration Training in Men after Myocardial Infarction

Abstract: The aim of the study was to evaluate the effects of the applied whole-body vibration training (WBV) as additional training to standard rehabilitation programme on exercise tolerance, evaluated through an exercise test, blood lipid profile, and the changes in selected echocardiographic parameters of patients after myocardial infarction. The study involved 63 males. The subjects were divided into two groups: standard—ST (27) and with vibration training—ST + WBV (36). All the subjects had undergone angioplasty wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In contrast, WBV was reported to increase tolerance to ischemia-reperfusion injury by reducing infarct size in rats (Shekarforoush and Naghii, 2019 ). On the contrary, in patients, although the significant improvement was seen after the standard exercise rehabilitation program, no extra effects of WBV were observed (Nowak-Lis et al, 2022 ). Both studies, however, were performed only on male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, WBV was reported to increase tolerance to ischemia-reperfusion injury by reducing infarct size in rats (Shekarforoush and Naghii, 2019 ). On the contrary, in patients, although the significant improvement was seen after the standard exercise rehabilitation program, no extra effects of WBV were observed (Nowak-Lis et al, 2022 ). Both studies, however, were performed only on male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarct size and severity of ventricular fibrillation were significantly lower in WBV at 1 and 3 weeks [ 160 ]. WBV has also been used as an adjunct to a cardiac rehabilitation program over a 24-days, both standard exercise rehabilitation and those who received adjunct WVB had improvement in exercise tolerance and left ventricular ejection fraction, and both groups obtained similar effects [ 161 ]. There are no published results on the use of WBV post CA, likely due to the need for subject cooperation and the critical nature of these patients.…”
Section: Whole-body Vibrationmentioning
confidence: 99%
“…Abbreviations: ↑ = increase, ↓ = decrease, MI = Myocardial Infarction, VEGF = vascular endothelial growth factor, TNF-α = tumor necrosis factor alpha, IL-1β = interleukin1-beta, IL-6 = interleukin 6, IL-17 = interleukin 17, IL-10 = interleukin 10, IL1-ra = interleukin 1 receptor antagonist, MCP-1 = Monocyte Chemoattractant Protein-1, sVCAM-1 = soluble Vascular Cell Adhesion Molecule-1, TIE2 = endothelial-specific receptor tyrosine kinase family, eNOS = endothelial derived nitric oxide synthase, NFƙβ-p65 = nuclear factor kappa beta p65 subunit, VF = ventricular fibrillation, LVEF = left ventricular ejection fraction, EF = Ejection Fraction. [ 100 , 101 , 102 , 103 , 114 , 115 , 116 , 117 , 121 , 122 , 125 , 126 , 128 , 129 , 133 , 134 , 138 , 139 , 140 , 141 , 143 , 160 , 161 , 162 , 166 , 172 , 175 , 177 , 178 , 179 , 182 , 183 , 184 , 185 , 186 , 188 , 189 ].…”
Section: Figurementioning
confidence: 99%
“…The WBV device is particularly helpful in individuals who are immobilized due to chronic health issues or have prolonged injuries, as typically seen in special needs, aging [22], overweight, and obese populations, as it is considered to be passive training, involving minimal risk of injury [23]. Prior research using WBV interventions have shown improvements in cardiovascular health [17,24], arthritis [25], flexibility [26], muscle soreness/stiffness [26], muscle strength/power [27], motor function and balance [28], and bone density [29] within mixed populations. However, to date, there is no published literature on the feasibility of WBV exercise training on autistic individuals or cardiovascular disease risk factors in sedentary and/or overweight individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%